Biosynthesis of factor V in isolated guinea pig megakaryocytes. - Chiu, H C (1985)
Although platelets contain Factor V, localized primarily in the alpha-granules, the origin of this coagulation cofactor in these cells is not known. We therefore explored whether isolated megakaryocytes could biosynthesize Factor V. Guinea pig plasma Factor V coagulant activity was demonstrated to be neutralized by human monoclonal and rabbit polyclonal antibodies directed monospecifically against human Factor V. These antibodies had been used earlier to purify human Factor V. These antibodies had been used earlier to purify human Factor V and to quantify Factor V antigen concentration, respectively (1983. Chiu, H. C., E. Whitaker, and R. W. Colman. J. Clin. Invest. 72:493-503). As determined by a competitive enzyme-linked immunosorbent assay with guinea pig plasma as a standard, Factor V solubilized from guinea pig megakaryocytes was present at 0.098 +/- 0.018 micrograms/10(5) cells. Each megakaryocyte contained about 500 times as much Factor V as is in a platelet (0.234 +/- 0.180 micrograms/10(8) platelets). The content of Factor V antigen in guinea pig plasma was greater (27.0 +/- 3.0 micrograms/ml) than that of Factor V antigen in human plasma (11.1 +/- 0.4 micrograms/ml). In contrast, human platelets contain ninefold more Factor V antigen (2.01 +/- 1.09 micrograms/10(8) platelets) than do guinea pig were 2.85 +/- 0.30 U/ml plasma, 0.022 +/- 0.012 U/10(8) platelets, and 0.032 +/- 0.03 U/10(5) megakaryocytes, compared with human values of 0.98 +/- 0.02 U/ml plasma and 0.124 +/- 0.064 U/10(8) platelets. Isolated megakaryocytes were found to contain Factor V by cytoimmunofluorescence. The megakaryocytes were incubated with [35S]methionine, and radiolabeled intracellular proteins purified were on a human anti-Factor V immunoaffinity column. The purified protein exhibited Factor V coagulant activity and neutralized the inhibitory activity of a rabbit antihuman Factor V antibody, which suggests that megakaryocyte Factor V is functionally and antigenically intact. These results indicate that Factor V is synthesized by guinea pig megakaryocytes. Nonetheless, megakaryocyte Factor V was more slowly activated by thrombin and in the absence of calcium was more stable after activation than was plasma Factor Va. Electrophoresis in sodium dodecyl sulfate and autoradiography of the purified molecule showed a major band of Mr 380,000 and a minor band of Mr 350,000, as compared with guinea pig and human plasma Factor V, where the protein had an Mr of 350,000. Both forms of Factor V were substrates for thrombin. Possible explanations for the higher molecular weight and different thrombin sensitivity and stability observed are that a precursor of Factor V was isolated or that the megakaryocyte Factor V had not been fully processed before isolation.